Hematological effects of benzene in the petroleum industry - Liao, Yen-Hsiung (International Journal of Health, 2015)
Purpose: To follow up the hematological changes in petroleum workers with continuous exposure to benzene.Approach: The hematological data of two petroleum company male employees was obtained from the annual health check-ups during 2001 to 2005. Workers were classified into exposed and unexposed groups on the basis of their exposure operation performed, and the industrial hygiene surveys.Results: There was not any difference between the exposed and the unexposed groups in the frequency of abnormalities with CBC differential and WBC differential almost. The frequency of higher than the normal range with eosinophils was significantly higher in exposed group (31.73%) than in unexposed group (11.54%, p < 0.05) in 1994, only.Conclusion: The study suggested that the eosinophil counts could be a hematological effect maker among workers exposed to benzene in the petroleum industry.